The Theater in the Educational Context: Elements of Strengths, Weaknesses, Opportunities, and Threats - Zaghloul, Hisham Saad (Journal of History Culture and Art Research, 2020)
Theater in education has gained global popularity since its creation. It employs the use of different forms of art to promote teaching and learning in schools. The practice has positively influenced the lives of school-going children. One importance derived from its application is the enhancement of students' communication skills. While the educational theater has received a positive light and adopted in many educational fronts, it has also encountered several challenges that have limited its effectiveness. This paper, therefore, seeks to uncover the reality behind theater application in schools by using SWOT analysis. The paper focuses on Egyptian education and schools as the case study. The questionnaire was implemented as a data survey tool in four Egyptian governorates, which included 186 experts and teachers in the various educational departments. The technique examines a given subject analytically and presents its strengths, weaknesses, opportunities, and threats. From the analysis results, it is observed that school educational theater enhances learners' self-esteem and promotes self-actualization. Several gaps were also pinpointed, including inadequate training among teachers and substandard content quality in the Egyptian education system and schools. The launching of the 2014-2030 educational strategic plans provided several opportunities for strengthening the effectiveness of educational theater. Possible erosion of students' moral values was among the threats identified when applying theatrics in the teaching and learning processes. The study concluded through its results the challenges facing the educational theater in Egypt, despite the problems of lack of funding, technical capabilities, and real opportunities to activate school activities in the educational field. The results of this study will provide an opportunity for different stakeholders in education to examine the nature of theater practices within their jurisdictions carefully, and hence formulate relevant policies to make the practice better and effective in driving the desired academic outcomes.